Identification of ferroptosis-related genes and predicted overall survival in patients with burns - Zhao, Mingjian; Zhang, Yetong; Zhao, Hongliang (Frontiers in Surgery, 2023)
Burns are a common trauma associated with considerable mortality and morbidity. Although a lot is known regarding burns pathogenesis, the involvement of ferroptosis is uncertain. Here we aimed to explore vital ferroptosis-related genes and molecules in burns, through bioinformatics analysis, to uncover new effective therapeutic targets. FerrDb database was used to acquire ferroptosis-related genes and GSE19743 was downloaded from Gene Expression Omnibus (GEO), a dataset with analysis of control and burned individuals. Hub genes were selected with Cytoscape software, and Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted. COX proportional hazard function and Kaplan-Meier survival analyses were implemented to screen prognostic related genes. Additionally, the miRWalk database was used to acquire the miRNAs relevant to our hub genes function and analyzed for enrichment. We identified 64 differentially expressed genes and through the intersection with ferroptosis-related genes, 10 were selected as hub genes. GO analysis revealed that the hub genes’ most enriched activities were response to oxidative stress, pyridine-containing compound metabolic processes, and reactive oxygen species metabolic processes. KEGG pathways analysis showed that these overlapped genes were enriched in several pathways, namely in VEGF signalling. Furthermore, the molecular miRNA’s functions significantly enriched were signal transduction and cell communication, namely the biological pathways of the glypican pathway and the ErbB receptor signaling network. SLC40A1 and GPT2 genes were found to be associated with overall survival, suggesting an important role in burn prognosis. This study may improve our understanding of the underlying burn mechanisms and provide a new direction for the prevention of poor outcomes, advances in burns treatment, and drug development.